Integrated Strategies to Enhance Entrepreneurial Intention During and After University: Islamic Entrepreneurship Perspective - Halim, Hendra; Kesuma, T. Meldi; Siregar, M. Ridha; Amir, Fakhrurrazi; Sari, Meutia Dwi Novita; Siregar, Fachrul A (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores strategies to enhance students' interest in entrepreneurship within the framework of Islamic entrepreneurship, emphasizing principles of justice, honesty, anti-usury, and social responsibility. Through a literature study methodology, the research delves into integrating Islamic values into academic curricula, establishing business incubators, providing seed capital, organizing Sharia-the-centric competitions, recognizing entrepreneurs' real achievements, and forming Muslim entrepreneur communities on campus. Entrepreneurs have found these strategies pivotal in cultivating a robust entrepreneurial spirit aligned with Islamic principles, contributing to individual student growth and broader economic and ethical development within the Muslim community. The study concludes with recommendations for universities and proposes avenues for advanced research to enrich this emerging field.